Fortalecimiento de la integración económica de la UNASUR desde una posible convergencia institucional de la CAN y el MERCOSUR - Romero Almeida, Diego Ricardo (2016)
In this research, the structure and institutions of the Andean Community, the Common Market of the South and the Union of South American Nations will be analysed, regarding the economic integration in the region. The main objective is to determine the possible converging structure in the Union of South American Nations. Furthermore, the aforementioned analysis includes the main areas of economic integration in the three systems of South American integration, in order to identify common interests. Moreover, in the way of strengthening the analysis in this research, some interviews to academics and government officials linked to economic integration will be also considered.